Green library: Reducing carbon footprints towards Sustainable Development in libraries: a Case Study of Federal College of Education Library, Zaria, Nigeria - Dada, Kayode Sunday John (Ciência da Informação em Revista, 2021)
Carbon footprint has become a popular way of communicating climate change issues and the need to change behaviour. Reduction of environmental burden or everyday environmental actions played an important role in the day-to-day activities of libraries. Libraries are in an excellent position to be both an ecological operator and promoter of environmental awareness. The methodology employed is survey. data collected was analyzed using decision mean of 3.00. findings from the study revealed that, libraries in Nigeria are not well ground on green library requirements, due to insufficient manpower, and tools. As a result of this, this study recommends that librarians must faces the challenge of finding solutions that adequately address these issues without compromising its economic development goals and the living standards of its people through environment awareness, communication strategies and reduction on environmental burden.